The Effectiveness of Using Quizizz in Improving Students' Collaboration Skills in the Course of Assessment of the Process and Results of Learning Chemistry - Ekaputra, Firdiawan (JUPE : Jurnal Pendidikan Mandala, 2025)
The purpose of this study was to determine the effectiveness of Quizizz in improving student collaboration. A one-group pretest-posttest design was used in this study. In this study, Quizizz was used in classroom learning with a project-based learning model. This study was conducted on 23 students in class R-001 who took the Chemistry Learning Process and Outcome Assessment course in the 2025/2026 academic year. Questionnaires were administered before and after the lectures. The hypothesis test results showed a significance value of 0.000 or less than 0.05. This indicates that the students' collaboration skills in this study increased significantly after using Quizizz.